Determinants of Taxpayer Compliance (Case Study at the Primary Tax Office of Serang Regency, Banten Province) - M. Fadhly; Apollo Daito (Universitas KH. Abdul Chalim Mojokerto, 2025)
Taxes are mandatory contributions imposed by the state on taxpayers for the benefit of the country. The purpose of this study is to determine the influence of Tax Audits (X1), Understanding of Tax Regulations (X2), and Strictness of Sanctions (X3) on Taxpayer Compliance (Y), and their impact on Tax Revenue (Z). For the research sample, the researcher conducted a survey of taxpayers registered at the Serang Barat Primary Tax Office. The data analysis tool used in this study was SPSS 22 software. The researcher used data from 100 respondents. The results of the study in submodel 1 indicate that Tax Audits and Understanding of Tax Regulations have a significant effect on taxpayer compliance, while the Strictness of Sanctions does not have a significant effect on taxpayer compliance. Submodel 2 shows that Taxpayer Compliance and Understanding of Tax Regulations have a significant effect on Tax Revenue, whereas the variables of Tax Audits and Strictness of Sanctions do not have an effect on Tax Revenue.